Ghrelin Ameliorates Traumatic Brain Injury by Down-Regulating bFGF and FGF-BP - Shao, Xuefei; Hu, Qianxin; Chen, Sansong; Wang, Qifu; Xu, Pengcheng; Jiang, Xiaochun (Frontiers in Neuroscience, 2018)
Traumatic brain injury (TBI) is a primary cause of disability and mortality. Ghrelin, a gastrointestinal hormone, has been found to have protective effects for the brain, but the molecular mechanism of these neuroprotective effects of ghrelin remains unclear. In this study, an electronic cortical contusion impactor was used to establish a rat TBI model and we investigated the effect of ghrelin on brain repair by neurological severity score (NSS) and histological examination. An antibody array was employed to uncover the molecular mechanism of ghrelin’s neuroprotective effects by determining the alterations of multiple proteins in the brain cortex. As a result, ghrelin attenuated brain injury and promoted brain functional recovery. After TBI, thirteen proteins were up-regulated in the brain cortex, while bFGF and FGF-BP were down-regulated after ghrelin treatment. It is known that bFGF can induce angiogensis in the brain and accelerate wound healing, which can be further enhanced by FGF-BP. Based on the previous studies, it is hypothesized that the exogenous ghrelin curing TBI might cause the closure of bFGF and FGF-BP functions on wound healing, or ghrelin might exert the neuroprotective effects by competitively inhibiting bFGF/FGF-BP-induced neovascularization. Whether the combinational administration of ghrelin and bFGF/FGF-BP can enhance or weaken the therapeutic effect on TBI requires further research.